1977
DOI: 10.1007/bf00292637
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation between a chromosome puff and the synthesis of a larval saliva protein in Drosophila melanogaster

Abstract: The structural gene Sgs-4 responsible for larval saliva protein 4 of Drosophila melanogaster was localized, with the help of Notch deficiencies, within the section between bands 3C10 and 3D1 of the X chromosome. In this chromosome section there is, very probably, only one fine band. In the third larval instar chromosome this section is transcriptionally active and forms a puff. When the ecdysone concentration increases, about 5 h before prepupa formation, it becomes inactive.--In section 3C of X chromosomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

1979
1979
1986
1986

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 23 publications
1
25
1
Order By: Relevance
“…However, in studying the 64C puff gene, Ashburner (10) found that when the chromosomes were unpaired in the 64C region in a particular hybrid nucleus, one chromosome puffed in the 64C region while the other remained condensed. On the other hand, Korge (12). found that at 3Cil, puffs formed on both chromosomes of hybrids except when the chromosome with the inactive 3C11 puff was heterozygous with the multiply inverted chromosome FM6.…”
Section: Resultsmentioning
confidence: 99%
“…However, in studying the 64C puff gene, Ashburner (10) found that when the chromosomes were unpaired in the 64C region in a particular hybrid nucleus, one chromosome puffed in the 64C region while the other remained condensed. On the other hand, Korge (12). found that at 3Cil, puffs formed on both chromosomes of hybrids except when the chromosome with the inactive 3C11 puff was heterozygous with the multiply inverted chromosome FM6.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being endoreplicated, homologues are aligned and paired in exact register. While the physiological significance of somatic chromosome synapsis remains unclear, a few instances of synapsisdependent phenotypes have been reported in Drosophila melanogaster (1)(2)(3)(4). "Transvection" is the term coined by Lewis (1) to describe the phenomenon of synapsis-dependent allelic complementation at the bithorax locus.…”
mentioning
confidence: 99%
“…This dependence on the ability of chromosomes to pair in order to produce a phenotype is known as transvection and has been observed for other loci (31,(34)(35)(36)(37). The results presented here show that there is no change in the size and no large change (if any) in the abundance of the white transcript we have identified when wild-type flies was also analyzed (rightmost four lanes) as a control for the proportionality of autoradiographic signal to RNA concentration.…”
Section: Results and Discussion Structure Of The Wild-type White Locumentioning
confidence: 81%